EFFECT OF PLANTING METHODS ON THE GROWTH AND YIELD OF COARSE RICE - T. Javaid; I. U. Awan; M. S. Baloch; I. H. Shah; M. A. Nadim; E. A. Khan; A. A. Khakwani; M. R. Abuzar (Journal of Animal and Plant Sciences, 2012)
An experiment was conducted to determine the effect of seeding techniques on growth and yield of rice. It was laid out in a randomized complete block design (RCBD) with split plot arrangements. Sowing methods (flat and bed) were assigned to main-plot while seeding techniques (dry seed drill, dry seed broadcast, soaked seed drill, soaked seed broadcast and conventional transplanting technique) were maintained in sub-plots. The results showed that higher paddy yield was obtained in flat sowing method as compare to bed sowing. Flat sowing also had maximum number of tillers and panicles with the highest unfilled spikelets. Among seeding techniques, conventional transplanting technique had maximum number of tillers and panicles per unit area, spikelets per panicle and paddy yield than other seeding techniques. Based on the results obtained, it can be concluded that conventional transplanting on flat is a better planting technique of rice under the agro-climatic conditions of Dera Ismail Khan.
Keywords: Rice; Oryza sativa; direct seeding; transplanting; yield.